2012
DOI: 10.1038/nsmb.2375
|View full text |Cite
|
Sign up to set email alerts
|

Controlling synaptotagmin activity by electrostatic screening

Abstract: Summary Exocytosis of neurosecretory vesicles is mediated bythe SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins syntaxin-1, synaptobrevin, and SNAP-25, with synaptotagmin functioning as the major Ca2+-sensor for triggering membrane fusion. Here we show that bovine chromaffin granules readily fuse with large unilamellar liposomes in a SNARE-dependent manner. Fusion is enhanced by Ca2+ but only if the target liposomes contain PI(4,5)P2 and if polyphosphate anions such as nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
247
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(263 citation statements)
references
References 53 publications
16
247
0
Order By: Relevance
“…Our data imply that the inhibitory effect of 5-IP 7 is more critical for a subset of vesicles with higher fusion activities, because the singlevesicle assay selectively monitors higher-activity vesicles (i.e., those that react within the given 30-s time window). Our observations indicate that 5-IP 7 at tens of micromolar concentrations exhibits a significant inhibitory effect in the presence of 1 mM ATP, which is also a pyrophosphate molecule (41). Therefore, it appears that the inhibitory effect of 5-IP 7 does not arise from simple electrostatic screening.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Our data imply that the inhibitory effect of 5-IP 7 is more critical for a subset of vesicles with higher fusion activities, because the singlevesicle assay selectively monitors higher-activity vesicles (i.e., those that react within the given 30-s time window). Our observations indicate that 5-IP 7 at tens of micromolar concentrations exhibits a significant inhibitory effect in the presence of 1 mM ATP, which is also a pyrophosphate molecule (41). Therefore, it appears that the inhibitory effect of 5-IP 7 does not arise from simple electrostatic screening.…”
Section: Resultsmentioning
confidence: 64%
“…Specifically, we used 3 mol percent (mol%) phosphatidylserine (PS) lipids for the v-vesicle membrane, while adding 15 mol% PS and 1 mol% phosphatidylinositol 4,5-bisphosphate (PIP 2 ) for the t vesicle. Moreover, we included 1 mM Mg 2+ ions and 1 mM ATP in the fusion reaction buffer to mimic the physiological concentrations of divalent ions and multivalent pyrophosphate molecules (41,44). Under these conditions, fusion kinetics, measured by the mixing of lipid dyes that constitute a FRET donor and acceptor pair [1,1′-dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine perchlorate (DiI) and 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindodicarbocyanine perchlorate (DiD)], was significantly accelerated at a Ca 2+ concentration of 100 μM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though EPR data agreed with this model of membrane bridging (24), and increasing evidence supports the notion that the membrane-bridging activity of synaptotagmin-1 is critical for its function (7,(25)(26)(27)(28)(29)(30)(31), a recent study concluded that the bridging occurs by a fundamentally different mechanism that requires trans interactions between synaptotagmin-1 oligomers bound to each membrane, without binding of the bottom of the C 2 B domain to the lipids (29). This mechanism, which we refer to as the oligomerization model, is compared in Fig.…”
mentioning
confidence: 77%
“…The clustering of C2 domains would act to localize this effect, perhaps enhancing curvature changes. The ability of Syt1 to promote curvature changes may in part be due to its ability to demix PS (54) and interact with lipids such as PIP 2 (52,55). By interacting with these charged lipids, Syt1 oligomerization would also influence the local composition of the bilayer, as well as the SNAREs, which have been observed to bind PIP 2 (56 -58).…”
Section: Discussionmentioning
confidence: 99%